Joan of Arc: A Reference Guide to Her Life and Works - Manning, Scott (Rowman & Littlefield Publishers, 2023)
Joan of Arc is the most recognizable woman from medieval Europe, yet the details of her life remain obscure to the general public while heavily debated by specialists. Rising from obscurity to insert herself into the court of French King Charles VII before marching with his armies to combat the enemies of the crown during the Hundred Years War, she was eventually captured, tried in an inquisition, and then executed as a relapsed heretic at the age of 19. Joan of Arc: A Reference Guide of Her Life and Works focuses on her life, and legacy. It features a chronology, an introduction offers a brief account of her life, a dictionary section lists entries on people, groups, places, events, topics, terms, and medieval documents central to Joan’s life including her letters, contemporary perspectives, her condemnation trial, and the nullification proceedings eventually blessed by the pope to overturn the verdict of the condemnation trial. This book aims to provide an understanding not just of Joan, but of the culture that produced and ultimately destroyed her.